Training load and subsequent wellness undertaken by an elite soccer goalkeeper: A case study report - Malone, J.; Jaspers, A.; Helsen, W.; Frencken, W. G. P.; Brink, M. S. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: The role of a goalkeeper is a unique but often overlooked position in soccer. Whilst the training load practices of outfield players has been examined in detail (Malone et al. 2015), such information in goalkeepers in relatively unknown. Therefore, the purpose of the present study was to quantify the training load undertaken by an elite professional goalkeeper. Methods: One male international elite goalkeeper participated in this study. Training load data was collected over an 8 week period during the in-season phase (two mesocycles) using a global positioning system (GPS) device, heart rate and session rating of perceived exertion (S-RPE). The following parameters were exported and analysed from the software: duration, total distance covered, average speed (total distance/total duration), high speed distance (> 5.5 m/s), high acceleration and deceleration efforts (> 3 m/s2), PlayerLoadTM and average heart rate. Data was assessed in relation to the number of days prior to a match (MD-). In addition, the subsequent total wellness was assessed using an adapted questionnaire from Hooper et al. (1995). Results: Duration, total distance, PlayerLoadTM and session-RPE were highest on MD-2, but remained similar across the remaining training days. Total wellness scores were highest on MD-3 (mean 21 au), but remained similar across the training microcycles (mean 17-18 au). There was no significant relationship between training load measures and the subsequent wellness response across all MD- days (P > 0.05). Discussion: This exploratory case-study provides novel data about the training load undertaken by a goalkeeper towards matches. The data suggest there is a limited relationship between training load measures and subsequent wellness in goalkeepers. Previous work has found large correlations between such measures (Buchheit et al. 2013) using parameters applicable to the athlete`s role (e.g. high speed distance covered in Australian Rules Football). The lack of relationship in the present study may be due to the lack of position-specific training load parameters we can currently measure in the applied context. Future work should look to utilise current wearable technology to generate goalkeeper-specific parameters in order to fully understand the loading profile at the elite level.